Molecular genetics in adult-onset Still’s disease: next-generation sequencing in 24 patients and literature review - Prieto-Peña, Diana; Labrador-Sánchez, Eztizen; Melero-González, Rafael B.; Antón-Pagés, Fred; Palmou-Fontana, Natalia; Alvarez-Reguera, Carmen; Paz-Gandiaga, Nerea; Blanco, Ricardo (Frontiers in Immunology, 2024)
ObjectiveNext-generation sequencing (NGS) panels are increasingly used for the diagnosis of monogenic systemic autoinflammatory diseases (SAIDs). However, their role in patients with adult-onset Still’s disease (AOSD) remains unknown. This study aims to assess the usefulness of NGS panels in AOSD patients to improve diagnosis and management of the disease.MethodsThis observational, multicenter study included all patients with AOSD diagnosis who underwent NGS panel testing in northern Spain. Clinical manifestations, laboratory parameters, complications, and therapeutic responses were recorded.ResultsA total of 24 patients (16 men, 8 women) with an average age of 42.2 ± 17.9 (mean ± SD) years, in whom NGS was performed, fulfilled the Yamaguchi and/or Fautrel criteria for AOSD. The most common symptoms, apart from fever, were skin rash (75%), asthenia (91.7%), and articular manifestations (91.7%). All patients had elevated acute-phase reactant levels and hyperferritinemia. Almost all patients received oral glucocorticoids as initial therapy. Conventional disease-modifying antirheumatic drugs (cDMARDs) were used in 17 (70.8%) patients and biologic therapy in 13 (54.1%) patients. Genetic variants were observed in 5 (20.8%) patients. None of them were classified as pathogenic. Variants of uncertain significance (VUS) were identified in NOD2 (c.2104C>T and c.2251G>A), TNFRSF1A (c.224C>T), TNFAIP3 (c.1939A>C), and SCN9A (c.2617G>A). Atypical manifestations and/or therapeutic refractoriness were observed in patients carrying genetic variants, except for one patient with the TNFAIP3 VUS. Four out of five patients with VUS had a severe and refractory course of the disease and required biologic therapy.ConclusionNGS was useful to rule out the presence of pathogenic genetic variants related to other SAIDs and to detect VUS that may help identify patients at risk for atypical and severe manifestations and poor response to conventional therapy.